2024
DOI: 10.3390/su16073034
|View full text |Cite
|
Sign up to set email alerts
|

Generative AI for Customizable Learning Experiences

Ivica Pesovski,
Ricardo Santos,
Roberto Henriques
et al.

Abstract: The introduction of accessible generative artificial intelligence opens promising opportunities for the implementation of personalized learning methods in any educational environment. Personalized learning has been conceptualized for a long time, but it has only recently become realistic and truly achievable. In this paper, we propose an affordable and sustainable approach toward personalizing learning materials as part of the complete educational process. We have created a tool within a pre-existing learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…LLMs are being used in various educational applications to enhance learning experiences and outcomes. For example, Pesovski et al [46] used ChatGPT, a type of LLM, to generate lesson plans and multiple-choice quizzes based on the learning outcomes provided by the professor for a particular class. These lesson plans were customized to different styles (traditional, with Batman references, or with Wednesday Addams' influence) to increase engagement.…”
Section: Llms In Educationmentioning
confidence: 99%
“…LLMs are being used in various educational applications to enhance learning experiences and outcomes. For example, Pesovski et al [46] used ChatGPT, a type of LLM, to generate lesson plans and multiple-choice quizzes based on the learning outcomes provided by the professor for a particular class. These lesson plans were customized to different styles (traditional, with Batman references, or with Wednesday Addams' influence) to increase engagement.…”
Section: Llms In Educationmentioning
confidence: 99%
“…Research has shown that ChatGPT can have several positive impacts on students' learning experiences. Recent studies (Pesovski et al, 2024;Hmoud et al, 2024) found that students exhibited increased motivation and engagement when interacting with the AI. The conversational nature of ChatGPT makes learning more interactive and personalized, capturing students' interest and encouraging active participation.…”
Section: Introductionmentioning
confidence: 99%
“…Atlas [22] reported the current application of Gen AI in HE as automated essay scoring; personalised tutoring; research assistance; language translation; helping professors in creating their syllabus, quizzes, and exams; generating reports; and email and chatbot assistance. Pesovski et al [23] added that Gen AI provides an opportunity for affordable and sustainable personalised learning. Other notable benefits of GenAI in HE are creative writing and brainstorming [24], support for personalised tutoring [13], support for pro-gramming code development [25], essay grading [26], and it is useful for designing science units and rubrics [27].…”
Section: Introductionmentioning
confidence: 99%